3.1 BILLION PKR PAKISTAN MORTGAGE REFINANCE COMPANY SUKUK: A FIRST OF ITS KIND FOR HOUSING FINANCE - Hasan, Dania (International Journal of Sukuk and Waqf Research, 2021)
The following presents a case study pertaining to innovation in the Sukuk industry in the Islamic capital market of Pakistan which has gained momentum over the last five years. The purpose of this case is to describe a recent Sukuk issued by Pakistan Mortgage Refinance Company (PMRC), a Mortgage Liquidity facility that issued Musharka Sukuk based on Shirkat-ul Aqd, aimed at developing housing finance market in Pakistan. Given the acute shortage of houses and reluctance amongst banks to grant consumers housing loans for a longer-term duration, this facility will enable affordable house financing through a Shariah-compliant mode, while offering a new avenue of investment for capital market participants. This paper describes the key features of the Sukuk, outlines its Shariah structure, and elaborates upon the mechanism of the transaction. A graphical illustration of the Sukuk structure is made to facilitate the reader’s understanding of each step of the transaction. The PKR 3.1billion PMRC Sukuk with the fixed-rate offering of 8.25% for 3 years is expected to be a landmark for the development of the housing sector of the country. It supplements the idea of how the issuance of Sukuk can play a vital role in addressing real economic needs. JEL Classification Codes:  G21, O18, Z23.